2019
DOI: 10.1002/jcb.28282
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin promotes cervical cancer tumorigenesis through activating FAK signaling pathway

Abstract: Cervical cancer is a cancer arising from the cervix, and it is the fourth most common cause of death in women. Overexpression of fibronectin 1 (FN1) was observed in many tumors and associated with the survival and metastasis of cancer cells. However, the mechanism by which FN1 promotes cervical cancer cell viability, migration, adhesion, and invasion, and inhibits cell apoptosis through focal adhesion kinase (FAK) signaling pathway remains to be investigated. Our results demonstrated that FN1 was upregulated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 39 publications
2
31
1
Order By: Relevance
“…Here, we suspect that FN1 is related to the pathway of ECM-receptor interaction. FN1 has been found to be highly expressed in esophageal and cervical cancers and associated with their prognosis [16][17][18]. In the present study, FN1, as a hub gene with the highest correlation with thyroid cancer, was highly expressed in tumor tissues compared with the adjacent non-tumor or normal tissues.…”
Section: Discussionsupporting
confidence: 51%
“…Here, we suspect that FN1 is related to the pathway of ECM-receptor interaction. FN1 has been found to be highly expressed in esophageal and cervical cancers and associated with their prognosis [16][17][18]. In the present study, FN1, as a hub gene with the highest correlation with thyroid cancer, was highly expressed in tumor tissues compared with the adjacent non-tumor or normal tissues.…”
Section: Discussionsupporting
confidence: 51%
“…Another study reported that high expression of FN1 was seen in invasive human bladder cancer T24 cells, and that inhibition of FN1 expression reduce the migration capacity of T24 cells through a mechanism related to targeted of pKC signaling pathway (13). In cervical cancer, high expression of FN1 activates the expression of pro-MMP-9, resulting in a signaling cascade (14). Thant et al reported that FN1 activated MMP-2 promoter, thereby increasing the expression of MMP-2 in ovarian cancer cell OVCA, while high expression of MMP-2 further enhanced the combination of OVCA cells and fibronectin which is broken down into small segments and cleavage receptor integrin.…”
Section: Discussionmentioning
confidence: 99%
“…The second passage of 1.0 Â 10 5 SMSCs was transfected with small interfering RNA (siRNA) as previously described [23]. SMSCs were placed into 6-well plates for 24 h. Cells were transfected with specific siRNA (Ambion, Huntingdon, UK) targeting FAK with Lipofectamine 2000 (Invitrogen, Carlsbad, CA, USA).…”
Section: Cell Transfection and Immunofluorescencementioning
confidence: 99%